MODEL OF CONTINUITY OF STAGES OF DEVELOPMENT OF MOTIVATIONAL READINESS COMPETENCE IN TEACHERS (American Journal of Interdisciplinary Research and Development, 2024)
The article covers the essence of the concept of modeling pedagogical education, its peculiarities, analyzes the issues of continuous professional development of teachers, research work carried out in the system of advanced training, and develops a model of stages of development of motivational readiness competence in teachers.